Development and Validation of Contextualized Strategic Intervention Materials in Science for Grade 6 Learners - Lituañas, Aljim B.; Cruz, Fe M. Dela (Randwick International of Education and Linguistics Science Journal, 2024)
This study aimed to develop a contextualized Strategic Intervention Material (SIM) in Science for Grade 6 learners at Tungao Central Elementary School, South Butuan District 2, Division of Butuan City, for the school year 2021-2022. Employing a quantitative research design, the study involved 91 respondents and two evaluators. The research instruments included four First Quarter Summative Tests, an Evaluation Instrument for Quality Assurance of the Contextualized SIMs, and an Evaluation Instrument for Content, Accuracy, Recency of Information, and Contextualization. Data analysis was conducted using frequency count, percentage distribution, and weighted mean. The findings revealed that the majority of learners did not meet expectations in their performance on the four summative tests. Specifically, many learners struggled with differentiating solutes from solvents, describing the appearance of a suspension, and explaining methods for separating mixtures through decantation and magnet use. The SIMs were designed and developed using guide cards, activity cards, assessment cards, enrichment activity cards, reference cards, and answer keys. These contextualized SIMs were evaluated based on quality assurance, content accuracy, recency of information, and contextualization criteria. Enhancements to the SIMs were made according to the validators' suggestions.